INVASIVENESS OF PHARMACOKINETIC STUDIES IN CHILDREN–A SYSTEMATIC REVIEW. Issue 1 (14th December 2015) - Altamimi, Mohammed; Sammons, Helen; Choonara, Imti
Abstract : Objectives: To compare the invasiveness of recent pharmacokinetic (PK) studies with older studies. The extent of this will be evaluated by analysing the number of samples and volume of blood collected in each study. Methods: A systematic literature review was performed to identify papers describing number of samples and volume of blood collected in studies of children (aged 0–18 years). The following databases were searched: Medline (1946 to May 2014), Embase (1974 to May 2014), International Pharmaceutical Abstracts (1970 to May 2014), CINAHL and Cochrane library. The keywords were "preterm neonate*" OR term neonate*" OR "neonate*" OR "new-born*" OR "child*" OR children OR "p*ediatric* OR "infant*" OR "adolescent*" AND "pharmacokinetic*" OR blood OR plasma OR specimen OR serum OR blood sampling OR blood sample*. Patients were grouped according to the guidelines of the International Conference of Harmonization (ICH), i.e. preterm neonates, term neonates, infants (28 days-under 2 years), children (2–11 years) and adolescents (12−≤18 years). Results: A total of 501 paediatric PK studies were identified between 1974 and 2014. Eighty eight studies were conducted between 1980 and 1990 (old studies), while 193 were conducted between 2004 and 2014 (new studies). Significantly more blood samples per child were collected in the old (median 8 [IQR: 6–11]) versus the new studies (median 7 [IQR: 5–9]) (p=0.002). In children the frequency of blood sampling was significantly higher in old studies (median 9 [IQR: 7–12]) compared to new studies (p=0.0002), but in the other age categories, there were no significant differences. There was no significant difference in the individual sample volume collected at each time point between two periods (p=0.913). However the total volume of blood collected for the study was significantly more in the old period (median=14 ml IQR [4.5–27.5 ml]) than in the new studies (median=11 ml, IQR [6–18 ml]) (p=0.040). Conclusions: Significantly more blood samples and larger total volumes of blood were taken in the old studies compared to new PK studies involving children. No major difference in the individual sample volume was seen.